PEMERINGKATAN E-GOVERNMENT INDONESIA (PEGI) DAN PEMANFAATAN TEKNOLOGI INFORMASI DI DKI JAKARTA - Lely Priska D. Tampubolon (Universitas Sriwijaya, 2016)
AbstractDKI Jakarta had the vision to create a modern and innovative city, capable of managing city resources effectively, efficiently and sustainably by optimizing ICT (Information and Communication Technology) in participatory governance in order to achieve a prosperous and cultured society. That called a smart city. DKI Jakarta provincial government has using ICT to provide information and public services. E-government performance can be assessed by some standards, which one is the e-government rankings Indonesia (PeGI). PeGI consists of five dimensions, there are two dimensions relating to ICTs, infrastructures and applications. The development of the wireless internet technology impacted on increase of a mobile device / smartphone user. The internet users in Jakarta in the majority used the telephone / mobile smartphone to access the Internet and government's mobile applications, such as Waze which widely use to monitoring traffic and help to searching alternatif way on traffic congestion. Utilization of information technology increases the provincial government's performance, as proved by the survey results and previous studies. For three consecutive years, 2012 until 2015, the performance of DKI Jakarta has increased, from the third ranking to the first ranking, and achieved a good performance appraisal. This achievement is inseparable from good IT governance.Keyword : e-Government ranking of Indonesia (PeGI), internet, Jakarta smart city, mobile-based applications, utilization of information technologyAbstrakDKI Jakarta memiliki visi untuk menciptakan sebuah kota modern dan inovatif, mampu mengelola sumber daya kota secara efektif, efisien dan berkelanjutan dengan mengoptimalkan TIK (Teknologi Informasi dan Komunikasi) dalam pemerintahan partisipatif dalam rangka mencapai masyarakat yang sejahtera dan berbudaya. Yang disebut kota pintar. Pemprov DKI Jakarta telah menggunakan TIK untuk memberikan informasi dan pelayanan publik. Kinerja E-pemerintah dapat dinilai dengan beberapa standar, yang satu adalah e-government peringkat Indonesia (PeGI). PeGI terdiri dari lima dimensi, ada dua dimensi yang berkaitan dengan TIK, yaitu infrastruktur dan aplikasi. Perkembangan teknologi internet nirkabel berdampak pada peningkatan pengguna perangkat/ ponsel smartphone. Para pengguna internet di Jakarta mayoritas menggunakan telepon/ ponsel smartphone untuk mengakses internet dan aplikasi mobile pemerintah, seperti Waze yang banyak digunakan untuk memonitor lalu lintas dan membantu untuk mencari jalan alternatif pada kemacetan lalu lintas. Pemanfaatan teknologi informasi meningkatkan kinerja pemerintah provinsi, seperti yang dibuktikan oleh hasil survei dan penelitian sebelumnya. Selama tiga tahun berturut-turut, 2012 sampai dengan tahun 2015, kinerja DKI Jakarta telah meningkat, dari peringkat ketiga ke peringkat pertama, dan mencapai penilaian kinerja yang baik. Prestasi ini tidak terlepas dari tata kelola TI yang baik.Kata kunci: aplikasi berbasis mobile, internet, Jakarta smart city, pemanfaatan teknologi informasi, Pemeringkatan e-Government Indonesia (PeGI)